Influence of Computer Technology on the Typefaces Design - Wang, Jin Lei (Applied Mechanics and Materials, 2014)
Computer technology has changed the way designers work, font design requires the use of computer technology. Designers are always subject design, how to effectively use the computer to use this tool for designers, rather than becoming a vassal of the computer. This article is in the current situation font design of the computer age, to explore how computer technology affects the font design.